Probing Bidirectional Plasmon‐Plasmon Coupling‐Induced Hot Charge Carriers in Dual Plasmonic Au/CuS Nanocrystals. Issue 12 (15th January 2023) - Bessel, Patrick; Niebur, André; Kranz, Daniel; Lauth, Jannika; Dorfs, Dirk
Abstract: Heterostructured Au/CuS nanocrystals (NCs) exhibit localized surface plasmon resonance (LSPR) centered at two different wavelengths (551 and 1051 nm) with a slight broadening compared to respective homostructured Au and CuS NC spectra. By applying ultrafast transient absorption spectroscopy we show that a resonant excitation at the respective LSPR maxima of the heterostructured Au/CuS NCs leads to the characteristic hot charge carrier relaxation associated with both LSPRs in both cases. A comparison of the dual plasmonic heterostructure with a colloidal mixture of homostructured Au and CuS NCs shows that the coupled dual plasmonic interaction is only active in the heterostructured Au/CuS NCs. By investigating the charge carrier dynamics of the process,  we find that the observed interaction is faster than phononic or thermal processes (< 100 fs). The relaxation of the generated hot charge carriers is faster for heterostructured nanocrystals and indicates that the interaction occurs as an energy transfer (we propose Landau damping or interaction via LSPR beat oscillations as possible mechanisms) or charge carrier transfer between both materials. Our results strengthen the understanding of multiplasmonic interactions in heterostructured Au/CuS NCs and will significantly advance applications where these interactions are essential, such as catalytic reactions. Abstract : Interacting plasmons: heterostructured Au/CuS nanocrystals exhibit localized surface plasmon resonance (LSPR) centered at two different wavelengths. Ultrafast transient absorption spectroscopy reveals a characteristic hot charge carrier relaxation associated with both LSPRs regardless of which LSPR is excited. A transient hot charge carrier response from non‐excited LSPRs is not known yet and contributes to a better understanding of dual plasmonic nanomaterials.